ChemInform Abstract: 2, 2, 4, 4‐Tetrathio Substituted 1, 3‐Dithietanes. Issue 25 (3rd June 2013) - Weber, Wolfgang; Chirowodza, Helen; Pasch, Harald
Abstract The title compounds (III) are formed by reaction of thiophosgene with carbonotrithioates or O‐ethyldithiocarbonates (I).